Komposisi Tubuh dan Durasi Tidur Subjek Dewasa Kelebihan Berat Badan dan Obesitas - Zakia Umami; Amalina Ratih Puspa; Elma Alfiah; Jasmine Nailufar Rachmah; Dwi Asri Fitryaningrum (Universitas Al Azhar Indonesia, 2026)
Obesity can be caused by poor sleep quality/duration. The purpose of this study was to analyze the relationship between body composition and sleep duration in overweight and obese adult subjects. The design of this study was cross sectional and was carried out for 8 (eight) months from March to October 2022. The data used in this study were weight and height data. Data on fat-free mass and fat mass were obtained through direct measurements using Inbody 270. The inclusion criteria for this study were adult men and women aged 18 to 65 years, Body Mass Index (BMI) of more than 25 kg/m2, Waist circumference > 80 cm , The number of research subjects is 32 people. The average age of the subjects was 27.34 years and almost all subjects were classified as young adults (18-40 years). More than half of the subjects had higher education and most of the subjects worked as private employees. Almost all research subjects had obesity nutritional status (84.4%). research subjects had body composition in the normal category for indicators of protein (66.0%), minerals (69.0%), FFM (72.0%), and SMM (66.0%). Meanwhile, most of the subjects were in the excess category for body composition indicators BFM (100.0%), BMI (100.0%), and PBF (100.0%). 40.6% of subjects had sleep duration of less than 7 hours. The results showed that there was no relationship between sleep duration and various indicators of body composition.Keywords - Body Composition, Fat Free Mass, Fat Mass, Obesity, Overweight, Sleep Duration.